Kelevan (Geneva, 1986)
"Assesses available data on the risks for human health and the environment posed by kelevan, a chlordecone derivative used in a number of countries as an insecticide, mainly for the control of the potato beetle and the banana root borer. The opening sections summarize what is known about the properties of kelevan, sources of exposure, environmental transport and distribution, levels in the environment, and kinetics and metabolism. A section devoted to the effects of kelevan on organisms in the environment concentrates on the findings from a very limited number of studies. In view of the sparsity of data on kelevan, the report bases its recommendations on what is known about the toxicity of chlordecone, concluding that, unless kelevan is indispensable, it should not be used."